Analisis Alur Novel Hello Karya Tere Liye - Jusalmen; Zuraida Khairani; Eva Fitrianti (JURNAL ARMADA PENDIDIKAN, 2025)
This study is motivated by the difficulty of realizing character education values in social life, indicating that character education as a foundation of national education has not been fully implemented in Indonesia. The purpose of this study is to describe the character education values found in the novel Hello by Tere Liye. This research uses a qualitative approach. The research instruments consist of the researcher, stationery, and tables used to record and transcribe all data related to character education values in the novel Hello by Tere Liye. The data collection technique used is documentation, while the data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of the study show that there are 13 forms of character education values, namely honesty, discipline, hard work, creativity, independence, democracy, curiosity, appreciation of achievement, communicativeness, love of peace, reading interest, social care, and responsibility. The most dominant character education value is curiosity, while the least dominant values are honesty and democracy. The character education values in the novel Hello by Tere Liye are presented through various techniques, namely dramatic and analytical techniques. These techniques make the story in the novel interesting and not monotonous to read. This indicates that the author is creative in constructing both the intrinsic and extrinsic elements of the novel.